A VOZ DO SILÊNCIO EM ANTES DE NASCER O MUNDO, DE MIA COUTO - Guedes, Alice (Revista Areia, 2023)
This is a review of the work Antes de nascer o mundo, of the mozambican writer Mia Couto. The present work uses the best-known edition of the book in Brazil, published by Editora Companhia das Letras, in 2016.